2010
DOI: 10.1111/j.1439-0531.2009.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Sows Fed ad libitum with a High Fibre Diet During Pregnancy

Abstract: The effect of ad libitum (ADLIB) feeding strategy on the fertility of the group housed sow was studied in a prospective field trial during 1.5 years. All study animals farrowed under standard farrowing circumstances in crates, and they were provided with an ad libitum feeding throughout the 30-day lactation. After weaning, animals were randomly allocated to one of the two dry sow feeding strategies (AD LIB or CONT). After oestrus detection in groups, they were artificially inseminated and moved into pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…A growing apart of the sow groups due to the different feed intake of the animals in an ad libitum feeding system was described by different authors [27,29,30], whereas Steffens [28] could not document any growing apart of the sows during pregnancy under ad libitum feeding when comparing the feeding systems. Peltoniemi et al [31] found no significant difference in BW and BFT of sows at the beginning of their study, which investigated the effect of ad libitum feeding on body condition development and fertility in comparison with a conventionally fed group. After the third lactation, the ad libitum fed sows were significantly heavier and had a significantly higher mean BFT.…”
Section: Discussionmentioning
confidence: 98%
“…A growing apart of the sow groups due to the different feed intake of the animals in an ad libitum feeding system was described by different authors [27,29,30], whereas Steffens [28] could not document any growing apart of the sows during pregnancy under ad libitum feeding when comparing the feeding systems. Peltoniemi et al [31] found no significant difference in BW and BFT of sows at the beginning of their study, which investigated the effect of ad libitum feeding on body condition development and fertility in comparison with a conventionally fed group. After the third lactation, the ad libitum fed sows were significantly heavier and had a significantly higher mean BFT.…”
Section: Discussionmentioning
confidence: 98%
“…Feeding diets containing high concentrations of fermentable NSPs to sows from weaning to estrus and during subsequent gestation periods for three reproductive cycles has been shown to increase the total piglets born and the born-alive litter size [ 112 ]. Studies have also shown that feeding certain types of high-fiber diets during specific phases of the reproductive cycle improves litter birth weights and weaning weights [ 113 , 114 ]. Collectively, although results from these studies indicate that feeding certain types and amounts of DF from common ingredients during specific phases of gilt and sow reproductive cycles can result in improved reproductive performance responses, results from other studies have not shown these benefits [ 108 ].…”
Section: The “Disconnect” Between Traditional Chemical Measurements and Physiological Responsesmentioning
confidence: 99%
“…Total litter birth weight and weaning weights were 0.87 kg and 3.59 kg greater respectively, in offspring of sows fed wheat straw compared to the offspring of control sows [ 52 ]. Sows fed ad libitum a diet enriched with sugar beet pulp, oat bran and oats, after weaning their first litter until the next lactation, weaned piglets that were heavier than those of control fed sows [ 54 ]. However, pregnancy rate, weaning to oestrus interval, the number of piglets born alive or number of stillborn piglets were not affected by treatment.…”
Section: Effects Of Dietary Fibre On Aspects Of Pig Productionmentioning
confidence: 99%